2023
DOI: 10.3389/fneur.2023.1186288
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes of ischemic stroke patients aged over 80 years treated with acute revascularization therapy according to pre-morbid disability: a PARADISE study

Abstract: IntroductionAging population leads to changes in the profile of patients with acute ischemic stroke (IS), and older adults were largely excluded from randomized clinical trials of acute revascularization therapy. This study aimed to assess functional outcomes of treated IS patients > 80 years old according to prior disability and identify associated factors.MethodsConsecutively older patients with acute IS treated with either IV thrombolysis and/or mechanical thrombectomy were enrolled between 2016 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(38 reference statements)
1
0
0
Order By: Relevance
“…Furthermore, most studies that have examined the functional prognosis of patients with acute stroke at hospital discharge have excluded those with premorbid disability, and the present results again support previous studies 13,29–31 . In patients with stroke with premorbid disability, premorbid mRS 24 and NIHSS at admission 32 affect the functional prognosis, and other studies have also reported premorbid mRS as a powerful prognostic factor 33,34 . Furthermore, poor premorbid functional status has been reported to be associated with odds of death within 1 year in intensive care unit patients over 85 years old, not only for stroke 35 .…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, most studies that have examined the functional prognosis of patients with acute stroke at hospital discharge have excluded those with premorbid disability, and the present results again support previous studies 13,29–31 . In patients with stroke with premorbid disability, premorbid mRS 24 and NIHSS at admission 32 affect the functional prognosis, and other studies have also reported premorbid mRS as a powerful prognostic factor 33,34 . Furthermore, poor premorbid functional status has been reported to be associated with odds of death within 1 year in intensive care unit patients over 85 years old, not only for stroke 35 .…”
Section: Discussionsupporting
confidence: 89%